Uso de um dispositivo confeccionado com materiais de fácil acesso para auxiliar na aprendizagem do conceito de propagação de calor aplicado no ensino médio - Barbosa, Suliene Alves (Universidade Federal de Roraima, 2019)
In this work, we developed experimental Physics classes with an educational device for heat spread applied to High School students of A School, located in Boa Vista city, the capital of the state of Roraima. We intended to enrich learning about heat propagation in order to understand the relationship between temperature, heat, thermal energy, heat flow and thermal balance. Considering this, we analyzed how the practical classes of Physics with the experimental device assembled from recyclable materials would contribute to the understanding and learning of students. We could observe that with the aid of experimental activity, the teaching process could make the learning process more efficient and enjoyable, thus contributing to improve the Physics teaching since it was observed that with the application of experiment in the classroom, students were more motivated, interested and curious about the subject. Overall, the survey results showed that when we used experiments in classroom as an educational tool, there was a significant evolution in the learning process because students showed a development in learning. We believe this research may help Physics teaching as one more pedagogical purpose centered on experimental practice with the need to redeem increasingly critical knowledge and reflections on the content addressed in class in the students. It is also important that the teacher can reflect upon how the student can understand and learn the concepts so that one can investigate, plan and develop strategies and ways to achieve significant learning. Thus, we conclude that students developed skills and competencies in content which involved the concepts related to heat spread. Regarding the steps of the application of the research, the students advanced and learned significantly.